Silver-Russell syndrome due to maternal uniparental disomy 7 and a familial reciprocal translocation t(7;13) - Behnecke, Anne; Hinderhofer, Katrin; Jauch, Anna; Janssen, Johannes W. G.; Moog, Ute (Clinical genetics, 2012)
Behnecke A, Hinderhofer K, Jauch A, Janssen JWG, Moog U. Silver-Russell syndrome due to maternal uniparental disomy 7 and a familial reciprocal translocation t(7;13). Silver-Russell syndrome (SRS) is a genetically heterogeneous disorder characterized by intrauterine and postnatal growth retardation, typical facial features and a spectrum of additional features including body and limb asymmetry and clinodactyly. Maternal uniparental disomy for chromosome 7 (upd(7)mat) was shown to occur in 5-10% of patients with SRS. Maternal UPD7 is clinically often associated with mild SRS. Parents of an affected child are given a negligible recurrence risk as all reported cases with upd(7)mat have been sporadic so far. In general, chromosomal rearrangements-like translocations increase the likelihood of uniparental disomy (UPD) for the chromosomes involved. However, SRS as the result of a upd(7)mat in association with an inherited chromosomal translocation involving chromosome 7 has only been reported once before. Here, we describe the second case of SRS with upd(7)mat due to a familial reciprocal translocation t(7;13). This emphasizes the importance of chromosome analysis in SRS patients with upd(7)mat to rule out chromosomal rearrangements despite their rare occurrence as they are of great relevance for genetic counseling of SRS families.